2015
DOI: 10.1093/toxsci/kfv114
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Made From Xyloglucan-Block-Polycaprolactone Copolymers: Safety Assessment for Drug Delivery

Abstract: Xyloglucan-block-polycaprolactone (XGO-PCL) copolymer nanoparticles have been proposed as nanocarriers for drug delivery. However, the possible harmful effects of exposure to nanoparticles still remain a concern. Therefore, the aim of this study is to evaluate the potential toxicity of XGO-PCL nanoparticles using in vitro and in vivo assays. Cytotoxicity and genotoxicity studies were conducted on MRC-5 human fetal lung fibroblast cells upon exposure to XGO-PCL nanoparticles. No significant reduction in the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 43 publications
0
43
0
2
Order By: Relevance
“…Corresponding quantitative analyses by UV–vis spectrophotometer revealed that the hemolysis rates of the NBOF‐P‐FA were all lower than 3% (Figure 4B), far lower than the critical safe hemolytic ratio set by ISO/TR7406. [ 22 ] These results identified its excellent hemocompatibility, making it possible for in vivo administration.…”
Section: Resultsmentioning
confidence: 97%
“…Corresponding quantitative analyses by UV–vis spectrophotometer revealed that the hemolysis rates of the NBOF‐P‐FA were all lower than 3% (Figure 4B), far lower than the critical safe hemolytic ratio set by ISO/TR7406. [ 22 ] These results identified its excellent hemocompatibility, making it possible for in vivo administration.…”
Section: Resultsmentioning
confidence: 97%
“…They evaluated the toxicity through in vitro and in in vivo assays. The results did not indicate toxicity effects, being the material able to act as nanocarriers for drug delivery [24].…”
Section: Introductionmentioning
confidence: 78%
“…9 , Figure S6 ). In short, the antibacterial peptides RGD-hylin a1 enriched to HMS-COOH were released after RGD-hylin a1-HMS targeted the tumor and achieved a synergistic effect of tumor inhibition with no side effects in vivo 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%